The radial forearm snake flap: An underutilized technique for fasciocutaneous and osteocutaneous forearm flaps with primary closure. Issue 5 (14th February 2022) - Gessert, Thomas G.; Pflum, Zachary E.; Thompson, James D.; Hoffman, Matthew R.; Sanchez, Ruston; Glazer, Tiffany A.; Wieland, Aaron M.; McCulloch, Timothy M.; Hartig, Gregory K.
Abstract: Background: The radial forearm free flap (RFFF) is associated with troublesome donor site morbidity related to split thickness skin grafting (STSG). The radial forearm snake flap with primary closure of the donor site may reduce donor site complications. Methods: Single institution, retrospective cohort study comparing rates of delayed donor site wound healing and tendon exposure in 52 patients undergoing radial forearm snake flap and 95 patients undergoing conventional RFFF with STSG closure of the donor site. Results: Tendon exposure occurred in zero (0%) patients undergoing snake flap and four (4.2%) patients undergoing conventional RFFF (0/52 vs. 4/95; p = 0.297). Delayed wound healing occurred in zero (0%) patients undergoing snake flap and 19 (20.0%) patients undergoing conventional RFFF (0/52 vs. 19/95; p < 0.001). Conclusions: The radial forearm snake flap provides an alternative to conventional RFFF harvest, which enables primary donor site closure with reduced rates of delayed donor site healing.